Observations and analysis of risk factors for GDV in a single institution: a case-control study - di Virgilio, Fabrizio; Rabaioli, Emanuela; Gualtieri, Massimo; Formaggini, Luca (Journal of Veterinary Healthcare, 2020)
Objective To evaluate/ determine the risk factors for dogs presented with Gastric Dilation- Volvulus (GDV) to a referral veterinary centre and to compare the results with those currently reported in veterinary literature. Materials and Methods The observational case-control study comprised a population of 215 dogs that attended the referral centre between 2000 and 2018. Medical records were searched for GDV and those matching the criteria were manually reviewed. A questionnaire was completed by the owners of the dogs involved in the study (both case and control populations) in order to gain further information that could be considered relevant to GDVs. In particular, information included the dogs’ behaviour and the dogs daily activities. Results The study included 115 cases of GDV and 115 controls. Out of the GDV dogs 13% (15/115) were small breed dogs and the remaining 87% (100/115) either large or giant breeds. The following risk factors for developing a GDV have been identified: Purebred dogs over 3 years old and either large of giant breeds, weighing > 30 kg. Foreign body ingestion, diarrhoea, and grass consumption were also associated to increase the likelihood in developing GDV. Behavioural temperament was not associated with developing GDV. Clinical Significance The findings support previously identified risk factors in the development of GDV, but characteristics related to the dogs temperament warrant further investigation. Knowledge of these results will further allow clinicians to make evidence‐based recommendations to owners in attempting to prevent GDV in dogs. Furthermore this paper confirms that the risk of GDV in certain breeds and in certain conditions is always high and that GDV is still an extremely current disease.
Keywords: Dog; Gastric Dilatation-Volvulus; Canine Gastroenteric; Gastroenterology; Stomach; Epidemiologic Factors.